Entrepreneurial Universities: The Role of Knowledge Service Innovation - Shahram Yazdani; Firouzeh Majidi; Snoor Bayazidi; Hamed Dehnavi (Acta Medica Iranica, 2022)
The complexity of today's world is constantly creating new challenges for higher education institutions, and they must continually be consistent and accountable to maintain standards of excellence and compete in international education markets. Being or becoming an entrepreneurial higher education institution is a response to these challenges. There is no "unique" approach, but there are different ways in which higher education institutions behave in an entrepreneurial and creative way. The purpose of this article was to explain how universities can become more entrepreneurial by changing how they provide knowledge. This article is based on the results of a literature review in the fall and winter of 2020 and is in line with the doctoral dissertation that is currently being done in the "Virtual School, Medical Education and Management, Shahid Beheshti University of Medical Sciences." After 1989, a review of the limited, focused literature on service innovation, with an emphasis on knowledge-based service innovation, was done. Service innovation is multidimensional and interactive in nature and can be examined from both technological (information and communication technology developments) and non-technological (organizational innovations) aspects. Accordingly, knowledge-based services include services based on professional knowledge and technology knowledge. Universities need to focus on innovation in both aspects of knowledge-based services. If universities are to become entrepreneurial universities, it is important to explain the comprehensive model of entrepreneurial universities by focusing on the dimensions, concepts, opportunities, challenges, and requirements for knowledge service innovation and then apply it to medical universities to fits their needs.